Modeling Turbulent Flow Velocity Profiles in Irregularly shaped Open Channels: A 3D Approach - Benoumessad, Kamel; Fourar, Fatima Zohra; Fourar, Ali; Massouh, Fawaz (Engineering, Technology & Applied Science Research, 2025)
Numerically simulating turbulent open-channel flows represents a formidable challenge in Computational Fluid Dynamics (CFD), particularly when addressing the interplay of transient turbulence, irregular bathymetry, and dynamic free-surface interactions inherent to natural river systems. This study advances a three-dimensional nonlinear (k-ε) turbulence model to resolve flow dynamics, velocity distributions, and mass transport mechanisms in both meandering and straight open channels. The framework leverages cylindrical coordinate systems to accommodate curvilinear geometries, enabling precise representation of intricate channel boundaries. The governing equations are discretized with the finite volume method, with pressure-velocity coupling achieved through the SIMPLE algorithm. The nonlinear (k-ε) formulation is uniquely suited to capture anisotropic turbulence effects while maintaining computational efficiency, addressing a critical gap in conventional isotropic eddy-viscosity models. Key innovations include the development of a geometrically adaptive numerical framework capable of simulating flow in meandering channels with variable curvature and width-to-depth ratios. Parametric analysis reveals that secondary circulations, driven by curvature-induced centrifugal forces and bed roughness heterogeneity, profoundly influence the velocity profiles and scalar transport. The model successfully predicts flow separation at bends, velocity-dip phenomena beneath free surfaces, and pollutant dispersion patterns in compound channels. Validations against empirical datasets confirm the model’s fidelity in replicating turbulent kinetic energy distributions and Reynolds stress anisotropy. This study establishes the nonlinear (k-ε) model as a versatile tool for analyzing hydraulically complex environments, including sediment-laden rivers and vegetated wetlands. By integrating geometric adaptability with advanced turbulence closures, the framework bridges theoretical CFD advancements and practical applications in flood risk mitigation, eco-hydraulic engineering, and contaminant transport modeling. The findings underscore the necessity of resolving anisotropic turbulence and secondary flow mechanisms to achieve predictive accuracy in real-world, geometrically heterogeneous open-channel systems.